Jean Cocteau - Arnaud, Claude,Mandell, Charlotte,Elkin, Lauren (Yale University Press, 2016)
Unevenly respected, easily hated, almost always suspected of being inferior to his reputation, Jean Cocteau has often been thought of as a jack-of-all-trades, master of none. In this landmark biography, Claude Arnaud thoroughly contests this characterization, as he celebrates Cocteau's
Keywords: Cocteau; Jean; Motion picture producers and directors; Authors; French; Artists